Food safety policy issues for developing countries - Unnevehr, Laurian J.; Haddad, Lawrence; Delgado, Christopher L. (International Food Policy Research Institute, 2003)
Food safety issues have attracted international attention because they play an increasingly important role in determining whether developing countries have access to export markets. At the same time, food suppliers in developing countries face the challenge of improving food safety for their growing urban middle classes, and the large burden of disease that poor food safety generates in developing countries is more widely appreciated. Because developing countries produce and consume more perishable foods than before, such as meat, milk, fish, and eggs, food safety has become especially important to domestic consumers and in trade among developing countries.... Food safety is no longer simply a public health issue. It is also a market development issue. The focus on food safety in international trade and in trade agreements has also made it a trade issue for many countries—developed and developing alike.